Macular Vascular Density Changes following Cataract Surgery in Diabetic Patients: An Optical Coherence Tomography Angiography Study - Le Feng; Guliqiwaer Azhati; Tingting Li; Fang Liu (Journal of Ophthalmology)
Purpose. Cataracts and diabetes very commonly coexist. The aim of the present study was to quantify the effect of uncomplicated phacoemulsification on retinal microvasculature in diabetic patients by using optical coherence tomography angiography (OCTA). Methods. A prospective observational study of diabetic and nondiabetic patients at baseline and 1 day, 1 week, 1 month, and 3 months after cataract surgery was performed by using OCTA. We measured the macular thickness (MT), superficial capillary plexus (SCP), deep capillary plexuses (DCP), and foveal avascular zone (FAZ) in the 3 × 3 mm macular images. Results. A total of 32 eyes of 32 type 2 diabetic patients and 40 eyes of 40 nondiabetic patients were assessed. There was a significant increase in MT at 1 month and 3 months after surgery in both groups (all P<0.05), but there was no significant difference between the two groups (P=0.217). At 3 months postoperatively, the SCP level in the diabetic group was significantly higher than that at baseline (P<0.05). The MT and SCP were negatively correlated with logMAR best-corrected visual acuity (BCVA), while the FAZ area and perimeter were positively correlated with logMAR BCVA in the diabetic group. Conclusions. Our study demonstrated that phacoemulsification can increase macular thickness in both diabetic and nondiabetic patients and increase SCP in diabetic patients within 3 months after surgery. Whether these changes persist for a longer period still needs to be investigated.